Pemanfaatan Sampah Anorganik Menjadi Produk Kreatif - Etika Sari; Merina Merina; Eka Lestari (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Anorganic waste is a type of waste that is very difficult to decompose and even takes a very long time, up to hundreds of years to fully decompose, especially cans and plastic which are difficult to biodegrade by nature. The purpose of this PkM activity is to overcome the problem of anorganic waste by reusing it. PkM activities are carried out by providing socialization to the community to increase knowledge in utilizing anorganic waste in the surrounding environment. The counseling material is an explanation of the recycling of anorganic waste into useful creative products, especially plastic and can bottles. The results of the socialization that has been carried out have increased public awareness of the use of anorganic waste which can be made into attractive and marketable products.